Optimization of Fast-dissolving Tablets of Ledipasvir-sofosbuvir Inclusion Complexes by Design of Experiments - Thummala, Uday Kumar; Maddi, Eswar Gupta; Avula, Prameela Rani (Indian Journal of Pharmaceutical Education and Research, 2023)
Background: Fast-dissolving tablets (FDTs) were aimed to be developed for the latest approved combination drugs for Hepatitis-C treatment, Ledipasvir (LDV) and sofosbuvir (SBV) which suffered with poor water solubility. Materials and Methods: Cyclodextrin (CD) complexation was done for the drugs to improve their solubility. The optimized CD complexes were taken for developing FDTs to improve dissolution limited bioavailability of these drugs. FDTs were developed by adopting design of experiments approach using Design Expert software. Type of β-CD, type of disintegrant and concentration of disintegrant were taken as the factors. Disintegration time, time for 90% dissolution of LDV and SBV were taken as the responses. The prepared tablets as per the selected experimental design were evaluated for the responses and also other characteristics like tensile strength, packing fraction, wettability. The results were analyzed by ANOVA and numerical optimization was performed with the desirability of minimizing all the responses. Results: All the selected factors were found to influence disintegration and dissolution times significantly. Dimethyl β-CD, croscarmellose sodium at 8% w/w was obtained as the optimized combination of the factors for the FDTs. The FTDs at this optimized combination of the factors were found to have 79.6 sec of DT, 17.72 and 13.68 min. of time for 90% dissolution of LDV and SBV respectively. Conclusion: These results which were significantly much better than those of the marketed tablets indicated that the FTDs were successfully developed using Design of experiments.
Keywords: Fast dissolving tablets; Hepatitis-C; Ledipasvir; Sofosbuvir; Optimization